Localization and Metabolic Activity of Mesenchymal Stromal Cells Within Solid and Liquid Core Alginate Beads - Nemyrovska, Yuliia V.; Tarusin, Dmytro M. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 174.